Budaya Politik dan Pendidikan - Luthfiyah Luthfiyah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: The occurrence of various crises in this nation allgedly stems from a crisis of conscience which almost all citizens,espicially entering the stakeholders in this country. Multimendisional crisis this nation will never be solved humanely if no action is carried our systematically and thoroughly. This paper describes how the process of political education in order to strengthen the power of conscience, how good the actual socialized education in political education in society and in educational institutions themselves to be able to restore the essence of the political aspects, and assist the establishment of a civilized nation. Keywords: Culture, Politics, and Education.